The Effect of Reward, Punishment, Work Environment, Incentives, and Work Discipline on Employee Performance at the Batu Aji Sub-District Office, Batam City - Utama, Martini Plantika Dwi; Ratnasari, Sri Langgeng; Susanti, Ervin Nora (Universitas Riau Kepulauan, 2025)
This study aims to determine the effect of rewards, punishments, work environment, incentives, and work discipline on employee performance at the Batu Aji Subdistrict Office, Batam City. Employee performance plays a very important role in the success of public sector services, so understanding the factors that influence it is very important. This study uses a quantitative approach with a survey method involving fifty employees as respondents. The data obtained were analyzed using multiple linear regression after being collected through questionnaires. The results showed that rewards, work environment, incentives, and work discipline had a significant effect on employee performance, while punishment had no significant effect. Rewards, work environment, incentives, and work discipline were proven to have the greatest partial effect on employee performance. These findings contribute theoretically to enriching the literature on factors that influence employee performance in the sector, as well as contributing practically to government management to pay more attention to these aspects in order to improve employee performance at the Batu Aji Subdistrict Office. However, this study has limitations in terms of the relatively small sample size, which should be expanded for broader generalization in future studies.